Study Of Diversity, Uniformity, And Dominance Of Macrophite Water Plants At Aek Batu Pematang Tambun Raya Beach Pematang Sidamanik District, Simalungun District, North Sumatra Province - Nainggolan, Dosy Maria Royeni; Sinaga, Mardame Pangihutan; Barat, Welmar Olfen Basten (Jurnal Ilmiah Platax, 2024)
Aquatic plants are part of the vegetation of these inhabitants in the earth, whose growth medium is water. The existence of aquatic plants that live well will increase aquatic productivity, and the role of aquatic plants is very important as a primary producer, as a habitat for biota such as fish, fish shelters, places to attach various animals and plants or algae. Transect method used is line transect with Quadrant 1 x 1 m. Data analysis includes diversity index, uniformity index and dominance index. Physical-chemical parameters include temperature, pH, dissolved oxygen and light intensity. The results found 3 species of aquatic plants Macrophytes vallisneria gigantea, Potamogeton crispus, and Myriophyllum spicatum. Diversity of aquatic plants macrophytes in coastal waters Aek Batu Tambun Raya District Pematang Sidamanik Simalungun classified as low with diversity index H' = 0.420-0.812 overall uniformity value of E = 0.5125 which falls into the category of labile, and the overall dominance of 0.7088 which is included in the medium category. Keywords:  aquatic plants macrophytes, diversity, uniformity, dominance. Abstrak Tumbuhan air merupakan bagian dari vegetasi penghuni bumi ini, yang media tumbuhnya adalah perairan. Keberadaan tumbuhan  air yang hidup dengan baik akan meningkatkan produktivitas perairan, dan peranan tumbuhan  air yang sangat penting adalah sebagai produsen primer, sebagai habitat biota seperti ikan, tempat perlindungan ikan, tempat menempel berbagai hewan dan tumbuhan  atau alga. Metode transek yang dipakai yaitu transek garis (line transect) dengan kuadran 1 x 1 m. Analisis data meliputi indeks keanekaragaman, indeks keseragaman dan indeks dominansi. Parameter fisik kimia meliputi suhu, pH, oksigen terlarut dan intensitas cahaya. Hasil penelitian ditemukan 3 spesies Tumbuhan Air Makrofita yaitu Vallisneria gigantea, Potamogeton crispus, dan Myriophyllum spicatum. Keanekaragaman tumbuhan air makrofita di perairan pantai aek batu tambun raya Kecamatan Pematang Sidamanik Kabupaten Simalungun tergolong rendah dengan indeks keanekaragaman H'= 0,420 – 0,812. Nilai keseragaman keseluruhan, yaitu E = 0,5125 yang masuk kedalam kategori labil dan dominansi keseluruhan, yaitu 0,7088 yang termasuk ke dalam kategori sedang. Kata kunci : Tumbuhan Air Makrofita, Keanekaragaman, Keseragaman, Dominansi.